Leucyl-tRNA synthetase deficiency systemically induces excessive autophagy in zebrafish - Masanori Inoue (Nature Portfolio, 2021)
Abstract Leucyl-tRNA synthetase (LARS) is an enzyme that catalyses the ligation of leucine with leucine tRNA. LARS is also essential to sensitize the intracellular leucine concentration to the mammalian target of rapamycin complex 1 (mTORC1) activation. Biallelic mutation in the LARS gene causes infantile liver failure syndrome type 1 (ILFS1), which is characterized by acute liver failure, anaemia, and neurological disorders, including microcephaly and seizures. However, the molecular mechanism underlying ILFS1 under LARS deficiency has been elusive. Here, we generated Lars deficient (larsb −/− ) zebrafish that showed progressive liver failure and anaemia, resulting in early lethality within 12 days post fertilization. The atg5-morpholino knockdown and bafilomycin treatment partially improved the size of the liver and survival rate in larsb −/− zebrafish. These findings indicate the involvement of autophagy in the pathogenesis of larsb −/− zebrafish. Indeed, excessive autophagy activation was observed in larsb −/− zebrafish. Therefore, our data clarify a mechanistic link between LARS and autophagy in vivo. Furthermore, autophagy regulation by LARS could lead to development of new therapeutics for IFLS1.